“Are You—?” “Are You?” Queer Advocacy at Contemporary Neoliberal Rape Crisis Centers - Chen, Melinda (Violence against women, 2023)
Antirape scholarship has largely focused on survivors and their needs. However, little is known about victim advocates, who support survivors, and how advocates’ identities can affect their work. This article draws on semistructured interviews with 23 LGBTQ+ advocates to explore how they navigate their sexual, gender, and racial identities at rape crisis centers today. Results show that LGBTQ+ advocates choose the ways that their sexual and gender identities are visible or invisible at their agency, usually to improve LGBTQ+ survivor services. By examining LGBTQ+ advocacy, this article critically evaluates normativity in antirape work and advocates for a queer transformation of rape victim services.